Supporting the Employment of Mothers: Policy Variation Across Fourteen Welfare States - Janet C. Gornick; Marcia K. Meyers; Katherin E. Ross (Luxembourg Income Study (LIS), 1996)
This paper compares fourteen industrialized Western countries - matched to microdata available from LIS - with respect to a subset of public policies that traditionally fall under the umbrella of 'family policy.' The analysis focuses on policies that facilitate the employment of mothers: parental leave, child care, and the scheduling of public education. Data on eighteen measures of public policy are presented and used to construct composite indices of national policy 'packages' that support employment for mothers with children of different ages.
Keywords: 330